Fiscal Independence Matters: Determinants of Local Government Financial Performance in Central Java - Royabafi, Muhammad Faiq La; Setyawan , Hendri (Journal of Principles Management and Business, 2025)
This study aims to analyze the influence of locally generated revenue (PAD), balancing funds, capital expenditure, and economic growth on the financial performance of local governments. The research is motivated by ongoing debates regarding the effectiveness of fiscal decentralization in improving regional financial outcomes and accountability. The study adopts a quantitative approach using secondary data from local government financial reports and regional economic indicators. Multiple regression analysis is employed to examine the relationships between the independent variables PAD, balancing funds, capital expenditure, and economic growth and the dependent variable, financial performance. The findings reveal that PAD and capital expenditure significantly enhance financial performance by strengthening fiscal independence and improving public service delivery. In contrast, balancing funds show a weaker effect due to their potential to foster fiscal dependency, while economic growth demonstrates an indirect and inconsistent impact. These results highlight the importance of optimizing PAD and prioritizing productive capital spending to strengthen regional fiscal capacity. The study contributes to policymaking by offering empirical evidence that supports the need for strategies to enhance local revenue generation and improve the allocation of capital expenditure. The novelty of this research lies in its integrative approach, which combines fiscal and economic indicators to evaluate financial performance using recent data, providing fresh insights into the dynamics of fiscal decentralization in local governance.